Piggy [videorecording (DVD)] - Pereda, Carlota; Salas, Claudia; Galan, Laura; Machi, Carmen; Holmes, Rick, 1963-; Castro, Pilar, 1970-; Aguilar, Camille; Pastor, José; Tatien, Fred (Magnolia Home Entertainment, 2023)
An overweight teen is bullied by a clique of cool girls poolside while holidaying in her village. A mysterious unknown man arrives in the village and kidnaps her tormentors. Someone has finally stood up for her. Sara sees it all: the blood, the mud, the knife, and the van in which he has taken them. And the unknown man has seen her. A wordless pact that neither will betray. She's an accomplice now. A series of crimes rock the village, and an investigation soon begins. The civil guard has endless questions, the villagers are suspicious and point fingers, the elderly neighbors' gossip. The heat is stifling, the pressure suffocating and her guilt torment her. What if she is found out? What's happened to the girls? What if the unknown man returns?